PERNIKAHAN DI BULAN MUHARRAM MENURUT PANDANGAN MASYARAKAT DESA CENTONG KABUPATEN MOJOKERTO - Yahya Sugiarti (JURNAL ILMIAH NUSANTARA, 2024)
This thesis aims to find out and explain the views of the people of Centong Village, Gondang District, Mojokerto Regency regarding the Abstinence of Marriage in the Month of Muharram which is believed by the people of Centong Village to be their tradition. This research uses a qualitative research type and uses an Islamic Legal Philosophy approach. The nature of this research is empirical because the object of this research is symptoms and phenomena that occur in society.The results of this research are: 1) The prohibition on marriage during the month of Muharram in Centong Village, Gondang District, Mojokerto Regency or also called the month of Suro is obeyed and trusted by Kejawen adherents due to several factors, namely following the customs of Javanese elders or according to Javanese people it is called snakes e wong era bien means a belief that is continuously held. 2) The prohibition on marriage during the month of Muharram fulfills the requirements for accepting urf as a legal source. So it can be said that the custom of prohibiting marriage during the month of Muharram is included in urf shahih. The most important thing is not to violate Sharia law, not to justify what is haram and not to cancel what is obligatory. And it can be concluded that this prohibition does not conflict with the urf category so that it can be carried out in everyday life and does not violate religious rules regarding believing in the prohibition of marriage in the month of Muharram.